Algae-based Dyes for the Textile Industry - Almoulki, Tasnim; Akkaya, Ebru (Mehmet Sinan Bilgili, 2022)
The applications of algae are becoming more popular day after day. From biofuels to nutrients, cosmetics, pharmaceuticals, and most recently dyes and ink. Due to algae's high lipid content that works best as a substitute for petroleum-based products, and because it is carbon negative and eco-friendly, algae-based dyes can present a transitional solution to the environmental damages caused by the dyeing phases in the textile industry. Scientists have investigated the types, methods, applications, and efficiency of various algae species and types of dyes to serve in various coloring and printing applications. In this paper, we explain the possibility of using microalgae as an ecofriendly dye for fabrics using common methods of dyeing backed with the related literature.
Keywords: Algae; dyes; dyestuff; environment; sustainable; textile; Engineering; Environmental Sciences & Ecology